2015
DOI: 10.1186/s12864-015-1778-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of host responses to avian influenza infection in ducks and chickens highlights a role for the interferon-induced transmembrane proteins in viral resistance

Abstract: BackgroundChickens are susceptible to infection with a limited number of Influenza A viruses and are a potential source of a human influenza pandemic. In particular, H5 and H7 haemagglutinin subtypes can evolve from low to highly pathogenic strains in gallinaceous poultry. Ducks on the other hand are a natural reservoir for these viruses and are able to withstand most avian influenza strains.ResultsTranscriptomic sequencing of lung and ileum tissue samples from birds infected with high (H5N1) and low (H5N2) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
131
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 104 publications
(168 citation statements)
references
References 46 publications
(73 reference statements)
7
131
1
Order By: Relevance
“…IFITM family is known to have a critical role in limiting AIV infection in chickens [114,115]. Clustering of gene expression profiles in chickens suggests that IFITM1 and 2 have an antiviral response and IFITM3 may act prior to viral membrane fusion and thus blocks viral entrance [114]. In physiological status, IFIRM5 is the main expressed IFITM in different embryonic and adult organs in chickens, except for the colon in which IFITM1 and 3 are the main expressed IFITMs.…”
Section: Interferon-stimulated Genes (Isgs)mentioning
confidence: 99%
See 1 more Smart Citation
“…IFITM family is known to have a critical role in limiting AIV infection in chickens [114,115]. Clustering of gene expression profiles in chickens suggests that IFITM1 and 2 have an antiviral response and IFITM3 may act prior to viral membrane fusion and thus blocks viral entrance [114]. In physiological status, IFIRM5 is the main expressed IFITM in different embryonic and adult organs in chickens, except for the colon in which IFITM1 and 3 are the main expressed IFITMs.…”
Section: Interferon-stimulated Genes (Isgs)mentioning
confidence: 99%
“…IFITM3 is a viral restriction factor, which targets influenza A virus entry process in humans by blocking complete virus envelope fusion with cell endosome membranes [115,118]. It has been suggested that the chicken IFITM3 protein protect host cells from infection with AIV to a similar level as its human orthologue and in vitro experiments showed the anti-influenza activity of IFITM3 in chicken cells [114]. Barjesteh et al in vivo study demonstrated the up-regulation of IFITM5 in the chicken trachea cells following CpG ODN and Pam3CSK4 treatments [49].…”
Section: Interferon-stimulated Genes (Isgs)mentioning
confidence: 99%
“…A particular interest in understanding what makes a species resistant or susceptible to a certain infectious disease has further led to a number of comparative immunological studies between different species of birds. Using transcriptomics, Smith et al (2015) found key differences in expression patterns of the interferon-induced transmembrane protein gene family in ducks and chickens, which the authors suggested might contribute to the large differences in susceptibility to AIV in these birds.…”
Section: Disease Studiesmentioning
confidence: 99%
“…This has been of particular interest in avian species that are known carriers of zoonotic diseases, as this gives an insight into how birds deal with these infections. A number of studies have used transcriptomics to study the immune response to infectious diseases such as avian influenza virus (AIV) in non-model species of birds (Huang et al 2013;Smith et al 2015;Vijayakumar et al 2015). A particular interest in understanding what makes a species resistant or susceptible to a certain infectious disease has further led to a number of comparative immunological studies between different species of birds.…”
Section: Disease Studiesmentioning
confidence: 99%
See 1 more Smart Citation